Peningkatan Pengetahuan Ibu Tentang Penanganan Pasca Imunisasi Bayi di Desa Matang Maneh, Kec. Tanah Jamboe Aye Kab. Aceh Utara 2024 - Futry Maysura; Zuhra Nabilla Putri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
deaths each year. An additional 1.5 million deaths could be prevented if global immunization coverage increased. Providing information to mothers can improve knowledge of post-immunization care for infants. The implementation method is through counseling on post-immunization care for infants, namely handling fever at home. This activity involves health workers at the Lhok Beuringen Health Center. This Community Service was carried out in Mataram Maneh village. The implementation time was in November 2024. Participants in this Community Service activity were mothers who had children aged 1-12 months in Mataram Maneh village with a total of 20 people. The activity was carried out in stages (1) providing an explanation of the purpose of the activity; (2) providing knowledge about the importance of immunization (3) providing knowledge about how to handle post-immunization impacts. The results of the activity showed that there was an increase in mothers' knowledge about post-immunization care for infants. After participating in this activity, mothers can apply this knowledge as much as possible to babies in post-immunization care for infants. The community service activity aims to educate mothers in Matang Maneh village, Tanah Jambo Aye District, North Aceh Regency, and to determine the level of knowledge of mothers about immunization and its benefits, the method I use is quantitative by distributing questionnaires after and before the presentation, the results of immunization counseling in Matang Maneh village, Tanah Jambo Aye District, North Aceh Regency, showed an increase. before being given counseling 30% knew, after counseling increased to 80%.